The duke's assassin : exile and death of Lorenzino de' Medici - Dall'Aglio, Stefano, 1970- (Yale University Press, 2015)
Stefano Dall'Aglio sheds new light on the notorious Florentine Lorenzino de' Medici (also known as Lorenzaccio) and on two of the most infamous assassinations in Italian Renaissance history. In 1537 Lorenzino changed the course of history by murdering Alessandro de' Medici, first duke of Florence, and paving the way for the accession of the new duke, Cosimo I. In 1548 Lorenzino was killed in Venice in revenge for the assassination. The events surrounding these murders, which Dall'Aglio reconstructs, involved the Medici, their loyalists, Florentine republican exiles, and some of the most powerful sovereigns of the time. The first publication in a century to examine the life of Lorenzino de' Medici, and the first work in English, this fascinating revisionist history is based on extensive research in the historical archives of Florence and Simancas. The tale is as gripping as a detective novel, as Dall'Aglio unravels a 500-year-old mystery, revealing who was behind the bloody death of the duke's assassin: the emperor Charles V.